2017
DOI: 10.1002/cite.201600161
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Flow‐Induced Aggregation and Conformational Change of Monoclonal Antibodies

Abstract: The aggregation process and conformational change of two monoclonal antibodies, monitored by in situ measuring techniques during stressing in a well-defined flow field, was experimentally studied. The increase in turbidity, which was detected by in-situ UV-vis spectroscopy, was attributed to the formation of aggregates. A stronger aggregate formation could be related to the higher exposure of hydrophobic groups, which was monitored by in situ fluorescence spectroscopy. Both presented techniques are powerful me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…There is thus a need to develop stress tests that more closely replicate the conformational ensemble generated during processing and transport. In light of this, we and others have shown that hydrodynamic extensional flow fields encountered during the nano-filtration, pumping, and fill-finish steps of bio-processing can trigger protein aggregation (Charm & Wong, 1981;Dobson et al, 2017;Simon, Krause, Weber, & Peukert, 2011;Wolfrum, Weichsel, Siedler, Weber, & Peukert, 2017). Using a reciprocating extensional and shear flow device (EFD) (Figure 1a), we showed that extensional flow fields can induce the conformational unfolding/remodeling of bovine serum albumin (BSA, Figure 1b), leading to aggregation that was characterized and quantified by an array of biophysical techniques including DLS, NTA, and TEM (Dobson et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…There is thus a need to develop stress tests that more closely replicate the conformational ensemble generated during processing and transport. In light of this, we and others have shown that hydrodynamic extensional flow fields encountered during the nano-filtration, pumping, and fill-finish steps of bio-processing can trigger protein aggregation (Charm & Wong, 1981;Dobson et al, 2017;Simon, Krause, Weber, & Peukert, 2011;Wolfrum, Weichsel, Siedler, Weber, & Peukert, 2017). Using a reciprocating extensional and shear flow device (EFD) (Figure 1a), we showed that extensional flow fields can induce the conformational unfolding/remodeling of bovine serum albumin (BSA, Figure 1b), leading to aggregation that was characterized and quantified by an array of biophysical techniques including DLS, NTA, and TEM (Dobson et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…The potential for hydrodynamic forces to induce mAb aggregation has long been of concern, with fresh attention being paid recently . Our efforts to address this inspired design of the EFD and its application to three IgG1s .…”
Section: Discussionmentioning
confidence: 99%
“…The potential for hydrodynamic forces to induce mAb aggregation has long been of concern, 9 with fresh attention being paid recently. 77 , 78 , 79 , 80 Our efforts to address this inspired design of the EFD and its application to three IgG1s. 59 , 60 With the above in mind, we set out to analyze the extent of EFD‐induced aggregation for a subset of 33 mAbs from the Jain et al dataset.…”
Section: Discussionmentioning
confidence: 99%